“Well, now, you asked them. Does that mean that they were expected to go?’: Master Narratives and Counter-Narratives in the Trial of Adnan Syed - Miruna Mihut, Andrea (Narrative Works, 2024)
A criminal trial in a traditional Western adversarial justice system is performed as a discursive battle of competing narratives between prosecution and defence. In the end, decisions by the judge and jury, while ostensibly premised on the strength of the evidence, rely in large part on the relative persuasive strength of the two stories – which one is more plausible? Commonsensical? Familiar? After exploring the positioning of narrative studies within the field of Criminology, this article will draw on ethnomethodology, talk-in-interaction, and narrative analysis to examine a trial that took place in the United States in 2000 – that of Adnan Syed. In order to appeal to cultural understandings shared by the American jury, trope stories were deployed by both sides. Prosecution told the story of Adnan Syed, a Jilted Muslim Lover, defending his honour after the victim broke up with him. Meanwhile, defence countered with a Star-Crossed-Lovers narrative, in which there was no motive for violence. I will argue that defence failed to deploy their story effectively and, in their attempts to counter the prosecution’s narrative, rather ended up reinforcing its terms. The triumph of the prosecution’s case may be found in the details of how the defence’s counter-narrative failed.